What Is The Process Of Resolving Disputes In International Business Law? - Respati, H. Radea; Sapsudin, Asep (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2024)
The complex global business landscape often creates conflict between entities, highlighting the need for efficient dispute-resolution mechanisms. Increased competition between countries can result in disputes that require immediate attention and require careful consideration of the structure of international and national communities. The importance of dispute resolution mechanisms is visible in the complexity of international business activities. This research aims to deepen a more essential understanding of alternative dispute resolution mechanisms in international business law. This objective is achieved by stating two research questions: the scope of resolving trade disputes and the alternative resolutions for international trade disputes. This is comparative qualitative research carried out in the literature concerning a normative juridical approach. Data was collected by searching relevant literature and legal materials for normative qualitative analysis. This research found that two types of disputes are commonly encountered in the legal process: disputes that are legal or can be resolved and conflicts that are political or cannot be resolved. Alternative Dispute Resolution (ADR) stands out for its effectiveness and efficiency in dispute resolution law. ADR aligns with the evolving dynamics of global trade, providing a valuable tool for managing disputes between business entities. Alternative. At least three alternative dispute resolution options can be chosen: (i) Resolving international trade disputes through mediation; (ii) Resolving international trade disputes through the World Trade Organization (WTO); Resolving disputes in international business through arbitration. This research suggests that it would be best to consider alternatives for resolving trade disputes according to the case's complexity level.